Organizational Justice and Employee Cynicism: Can Trust Mediate? - Khan, Ryan Basith Fasih; Firmansyah, Bagas Adi (Jurnal Minds: Manajemen Ide dan Inspirasi, 2024)
This study examines how employee cynicism, characterized by negativity, skepticism, and distrust, can hinder productivity and organizational success. To understand this phenomenon in public organizations, we surveyed 163 public servants in East Java, Indonesia. We analyzed the data across different organizational sizes, performance levels, and strategic goals using an exploratory-based structural-equation model. Our findings reveal three key points. First, employees experience less cynicism when they perceive fairness, equality, and transparency in the workplace, highlighting the importance of organizational justice. Second, employee trust acts as a protective factor, further reducing cynicism. Finally, employee trust mediates the relationship between organizational justice and cynicism, suggesting that fostering trust strengthens the link between fair treatment and positive employee attitudes. These results emphasize the importance of staff departments and leadership promoting both organizational fairness and trust to create a healthier and more productive work environment.